Legal regulation of restricting the rights of police officers in the context of recruiting for the service to the National Police of Ukraine (Bulletin of Kharkiv National University of Internal Affairs, 2018)
The author has analyzed the norms of the Law of Ukraine “On the National Police” concerning the establishment of restrictions of the rights of police officers due to their service within the National Police of Ukraine. The advisability of implementing appropriate restrictions has been studied. Overall support for establishing restrictions for police officers with some reservations about some of them has been stated. It has been indicated that police officers performing law enforcement function of the state, use a wide range of powers and, if the rights of this category of employees are not limited in a certain way, then there is a risk of conflict of interest, corruption and abuse of power by police officers.The author has provided propositions to improve national legislation, which establishes restrictions of the rights of police officers due to the relevant service. The author proves the feasibility of wording the Art. 66 of the Law of Ukraine “On the National Police” as follows: “A police officer while the service can not be engaged in any other paid activities, except for scientific and educational, research and creative activities, medical practice, sports instructor and judge practice”. The author has also grounded the need to amend p. 5 of the Art. 61 of the Law of Ukraine “On the National Police” with the following sentence: “If there is a threat to life and health of a police officer, as well as life and health of their family members, caused by non-payment of salaries and violation of labor rights by leadership of the police force, the police officers are allowed to strike, ensuring the rights and freedoms of other people”.
Keywords: restrictions; candidate for the service; police force; political parties; secondary employment; strike.